Long-Term Follow-Up of Lichtenstein Repair of Inguinal Hernia in the Morbid Patients With Self-Gripping Mesh (ProgripTM) - Zhang, Weiyu; Zhao, Yixin; Shao, Xiangyu; Cheng, Tao; Ji, Zhenling; Li, Junsheng (Frontiers in Surgery, 2021)
Objective The aim of this study was to demonstrate the safety and the efficacy of the self-gripping mesh (ProgripTM) for inguinal hernia repair in morbid patients of higher American society of anesthesiologists (ASA) classification (ASA III&IV). The incidence of chronic pain, post-operative complications, and hernia recurrence were evaluated. Methods Data were collected retrospectively from patient files and were analyzed for 198 hernias in 147 patients. All patients included in this study had undergone inguinal hernia by Lichtenstein approach with the self-gripping mesh (ProgripTM) in the same clinical center. Pre-, peri- and post-operative data were collected, and a long-term follow-up of 31.8±19.5m (5-60m) was performed. Complications, pain scored on a 0–10 numeric rating scale (NRS), and hernia recurrence were assessed. Results During the past five years, 198 hernias in 147 patients were repaired with Lichtenstein technique with the self-gripping mesh (ProgripTM). The majority of patients were high level of ASA classification (95.9%), with ASA III (10.2% ) and IV (85.7%). The mean operation time was 71.2±23.8 min. The mean length of postoperative stay was 2.5±2.1 days. There were no intra-operative complications. 14 cases (7.1%) suffered post-operative surgical wound complications, which were limited to skin and subcutaneous tissue, there was no mesh infection, the acute postoperative pain was low or mild (VAS score ≤4), and the chronic postoperative pain was reported in 3 patients (1.5 %) and tolerable , hernia recurrence occurred in one patient during the follow-up period. Conclusion This study demonstrated that high-risk patients (ASA III & IV) with inguinal hernia can be repaired with Lichtenstein procedure with the self-gripping ProgripTM mesh safely, with low pain and low hernia recurrence rate.